Philosophical analysis of the formation of the spirituality of modern Kazakh youth - P., Müürsepp; Dussipova A.S., Ramazanova A.Kh., (Opción, 1970)
The aim of the article is to determine the role and the influence of the global informational network on spiritual life and goal setting of young people via comparative qualitative research methods. As a result, one of the most reliable instruments of the prevention of the negative youth deviations is the implementation of culturally-based projects with an analysis of the heritage of the Republic of Kazakhstan. In conclusion, the complex approach would develop students’ goal setting for the solution of not virtual, but real spiritual problems.